Principles, structure and taxonomic units in the russian and international (WRB) systems of soil classification - M. I. Gerasimova (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
Two classification systems under comparison differ in objects, terminology, hierarchical levels, and approaches to identify soils. However, they have some common features: both systems are oriented to soil properties and apply the pedogenetic concepts, on one hand; on the other hand, the results, namely, some of the soil taxonomic units are similar. The second-level units of WRB, representing the classification rather than the reference base, display a certain correlation with the subtype level in the Russian soil classification system. This level in two systems may be qualified as a really active, and it contains the most complete genetic characteristic of a soil; moreover, there is a similarity in criteria for qualifiers in WRB and genetic features (producing subtypes) in the Russian system. The difference between two classification systems is manifested in the number and essence of diagnostic horizons because they perform different functions. In the International system, they mainly serve for recognition of soils (in the key), while they directly identify genetic soil types in the Russian system.